α1-Antichymotrypsin Present in Therapeutic C1-Inhibitor Products Competes with Selectin–Sialyl LewisX Interaction - Engel, Ruchira; Delvasto-Nuñez, Laura; Roem, Dorina; van Mierlo, Gerard; Holst, Stephanie; Hipgrave Ederveen, Agnes L.; van Buul, Jaap D.; Wuhrer, Manfred; Wouters, Diana; Zeerleder, Sacha (Thrombosis and Haemostasis, 2018)
Background C1-inhibitor (C1-inh) therapeutics can reduce neutrophil activity in various inflammatory conditions. This ‘novel’ anti-inflammatory effect of C1-inh is attributed to the tetrasaccharide sialyl LewisX (SLeX) present on its N-glycans. Via SLeX, C1-inh is suggested to interact with selectins on inflamed endothelium and prevent neutrophil rolling. However, C1-inh products contain plasma glycoprotein α1-antichymotrypsin (ACT) as a co-purified protein impurity.Objective This article investigates the contribution of ACT to the effects observed with C1-inh.Materials and Methods We have separated C1-inh and ACT from a therapeutic C1-inh preparation and investigated the influence of these proteins on SLeX–selectin interactions in a specific in vitro model, which makes use of rolling of SLeX-coated beads on immobilized E-selectin.Results We find that ACT and not C1-inh, shows a clear sialic acid-dependent interference in SLeX–selectin interactions, at concentrations present in C1-inh therapeutics. Furthermore, we do not find any evidence of SLeX on C1-inh using either Western blotting with anti-SLeX antibodies (CSLEX1 and KM93) or by mass spectrometric analysis of N-glycans. C1-inh reacts weakly to antibody HECA-452, which detects a broad range of selectin ligands, but ACT gives a much stronger signal, suggesting the presence of a selectin ligand on ACT.Conclusion The ‘novel’ anti-inflammatory effects of C1-inh are unlikely due to SLeX on C1-inh and can in fact be due to SLeX-like glycans on ACT, present in C1-inh products. In view of our results, it is important to assess the role of ACT in vivo and revisit past studies performed with commercial C1-inh.
Keywords: inflammation; selectins; glycosylation; C1-inhibitor; sialyl-LewisX